Ag/AgCl Reference Electrode Based on Thin Film of Arabic Gum Membrane - Sagir Alva; Aiman Sajidah binti Abdul Aziz; Mohd Ismahadi bin Syono; Wan Adil bin Wan Jamil (Universitas Gadjah Mada, 2018)
The Ag/AgCl reference electrode based on the Arabic Gum (AG) hydrogel films was successfully developed. The Arabic Gum concentration used in this study was 10–40% (w/v) with an optimum concentration of 20% (w/v). In this study, reference electrode performance testing is based on DmV response of Cl-ion’s measurements, stability tests and performance testing against ISE sensors such as K+, NH4+, and NO3-. The Ag/AgCl based reference electrode of the Arabic Gum film shows an average DmV of 4.0 ± 0.7 mV when response test is performed against a standard Ag/AgCl double junction electrode in various concentrations of Cl-ion’s. Meanwhile, in stability testing conducted in a 0.01 M KCl solution for 72 h found drift of < 0.6 mV/h. The reference performance test of the Arabic Gum reference electrode with three types of ISE NH4+, K+ and NO3- commercial sensors obtaining a slope closer to the Nernst value is 54.9 ± 0.9, 52.3 ± 0.5 and -53.2 ± 0.2 mV/dec with all having a linear distance of 0.1–10-5 M.